Image, Perception, and the Making of U. S. -China Relations - Li, Hongshan (Hamilton Books, 1998)
Image, Perception, and the Making of U.S.-China Relations examines major events in the history of the relationship between the U.S. and China to show the development and effects of national images and perceptions. These essays expose the effects of ideology as represented through foreign policy and the actions of leaders, as well as the role of the media and governments in shaping public opinion and attitudes. They show the evolution of the influential forces from the nineteenth century through the twentieth century. In each country, a small group of people has always controlled these forces by manipulating the power of the media and governments. The nature of this situation changed national perceptions as power often moved from one small group to another. As a result of manipulating the images and perceptions of each country, these biased and untrue views have inevitably led to conflict between the two countries.